2015
DOI: 10.1007/s00345-015-1583-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and outcomes in primary urethral cancer: results from the international collaboration on primary urethral carcinoma

Abstract: These data suggest that clinical nodal stage is a critical parameter for outcomes in PUC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 11 publications
(21 reference statements)
2
45
0
1
Order By: Relevance
“…Our present study shows that the incidence of PUC was higher in men (63.4%), which is consistent with findings that 66.6% of men have a threefold higher incidence of PUC compared with women 13. In contrast, studies of 344 patients with PUC included in European cancer registries14 and a multi-institutional study of 154 patients with PUC6 did not detect a difference in OS between women and men. The median OS values of men and women were 21 months and 20 months, respectively, which supports the conclusion that women and men with PUC may experience similar durations of survival.…”
Section: Discussionsupporting
confidence: 92%
“…Our present study shows that the incidence of PUC was higher in men (63.4%), which is consistent with findings that 66.6% of men have a threefold higher incidence of PUC compared with women 13. In contrast, studies of 344 patients with PUC included in European cancer registries14 and a multi-institutional study of 154 patients with PUC6 did not detect a difference in OS between women and men. The median OS values of men and women were 21 months and 20 months, respectively, which supports the conclusion that women and men with PUC may experience similar durations of survival.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence is higher in males and onset age is commonly in the 60s in both males and females. Regarding the histologic type, urothelial cancer is most frequent, accounting for 47–65% of cases, while squamous cell carcinoma accounts for 16–30%, although squamous cell carcinoma was the most frequent in males and females in one study …”
Section: Discussionmentioning
confidence: 90%
“…Clinical nodal stage, tumor location and presence of synchronous BC were the only parameters found to be independently associated with RFS. Importantly, we recently reported that clinical nodal stage is a strong predictor for outcomes in primary urethral cancer [10] . As the number of events was low (n = 26 death events), we did not perform a multivariable analysis for OS.…”
Section: Discussionmentioning
confidence: 99%